2022
DOI: 10.1039/d2tc02043b
|View full text |Cite|
|
Sign up to set email alerts
|

A morphology-dependent lattice stability investigation in ZnS nanostructures by high-pressure XAFS studies

Abstract: The morphology-dependent behavior of nanomaterials under high pressure has always been a research hotspot due to its great importance in materials science and physical science fields. Here, we performed in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The normalized lattice parameters a/a 0 and c/c 0 and the cell volume of the WZ structure decrease with increasing pressure and exhibit an anisotropic compression behavior, accompanied with the shortening of the Zn−S (or Mn−S) bond distance until the phase transition occurs (Figure S3). 57,58 The observed results indicate that the Mn 2+ and Eu 3+ dopants have negligible influence on the structural stability and lattice compressibility of the host structure. However, the shrinkage of the unit cell volume and lattice parameters a and c for the WZ structure with increasing pressure implies the shortening of the bond distances between the anions and cations and enhanced interactions between the doped luminescent ions and host lattice.…”
Section: Characterization Of Synthesized Mn and Eumentioning
confidence: 83%
“…The normalized lattice parameters a/a 0 and c/c 0 and the cell volume of the WZ structure decrease with increasing pressure and exhibit an anisotropic compression behavior, accompanied with the shortening of the Zn−S (or Mn−S) bond distance until the phase transition occurs (Figure S3). 57,58 The observed results indicate that the Mn 2+ and Eu 3+ dopants have negligible influence on the structural stability and lattice compressibility of the host structure. However, the shrinkage of the unit cell volume and lattice parameters a and c for the WZ structure with increasing pressure implies the shortening of the bond distances between the anions and cations and enhanced interactions between the doped luminescent ions and host lattice.…”
Section: Characterization Of Synthesized Mn and Eumentioning
confidence: 83%
“…The other type of inter‐lath carbide is a strip‐shaped M 7 C 3 carbide with a hexagonal close‐packed (HCP) structure. [ 25 ] M 7 C 3 is a Cr‐rich carbide. Notably, the strip‐shaped M 7 C 3 carbide in HWD700 steel has a width of 12 ± 3 nm.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Liu et al observed that Wurtzite (WZ)-structured ZnS nanorods (NRs) transformed to the rock salt (RS) structure at 19–20 GPa without going through a ZB structure. This is in contrast to the WZ → ZB → RS phase transition observed in bulk ZnS and spherical ZnS NPs . The same group also reported that GaAs nanowires (NWs) (40 nm in diameter) show larger bulk moduli and enhanced ZB to orthorhombic (OR) phase transition pressure compared with those of the bulk material.…”
Section: Pressure-induced Inorganic Np Atomic Structure Phase Transitionmentioning
confidence: 88%
“…This is in contrast to the WZ → ZB → RS phase transition observed in bulk ZnS and spherical ZnS NPs. 39 The same group also reported that GaAs nanowires (NWs) (40 nm in diameter) show larger bulk moduli and enhanced ZB to orthorhombic (OR) phase transition pressure compared with those of the bulk material. The phase transition pressure of 20 GPa is close to that reported for GaAs NWs with diameters from 80 to 150 nm.…”
Section: Semiconductor Npsmentioning
confidence: 98%